Methodological Approach of Reviving Zakat and Waqf Institutions in Bauchi and Gombe States Nigeria: The Way Forward - Hussaini, Hamza Abubakar; Muhammad, Adamu Abubakar; Muhammad, Zuwaira Jibril; Aliyu, Shafa’atu Ahmad (Universitas Darussalam Gontor, 2024)
This paper examines the Methodological Approach of Reviving Zakat and Waqf Institutions in Bauchi and Gombe States Nigeria by assessing the current situation of Zakat and Waqf institutions in Bauchi and Gombe States, Nigeria, and proposes measures for their revival for human sustainable development. The paper also discusses a brief history of Zakat and Waqf in Islam and their significance in promoting social welfare of the Ummah, as well as the current challenges faced by these institutions in the study area which includes a lack of establishment willingness, proper management, low patronization, inadequate funding, and limited public awareness. This research adopted the qualitative research method by using a literature review and interview for data collection as well as content analysis for analyzing the data. In order to revive these institutions and fully harness their potential, the paper suggests a holistic approach that involves collaboration between government institutions, religious organizations, and the community. This approach includes developing a comprehensive legislative framework for Zakat and Waqf, establishing an effective management system, and increasing public awareness through education and outreach programs.